Ресурсно-діяльнісний підхід як основа формування конкурентного статусу підприємств машинобудування - Терованесова, Олександра Юріївна (Одеський національний університет ім. І. І. Мечникова, 2015)
Обґрунтовано доцільність застосування ресурсно-діяльнісного підходу у формуванні конкурентного статусу підприємств машинобудування, що органічно пов'язано з основними завданнями, які постають перед сучасними підприємствами. Визначено взаємозв'язок конкурентного потенціалу та конкурентних переваг підприємства, що водночас об'єднує їх трирівневі зв'язки. Доведено, що основою формування конкурентного статусу є конкурентний потенціал підприємства. Визначено, що конкурентний статус підприємства характеризує достатність передумов досягнення ним певного рівня конкурентної переваги та залежить від ефективності використання ресурсів.

The article analyses applicability of resource and activity approach on the base of the competitive status formation of machine building enterprises which are organically connected with the main tasks the modern enterprises face. The true relationship of competitive opportunities and competitive advantages of the enterprises is defined and it unites their three-tier connection. It is proved the basis of the competitive status formation is the competitive opportunities of the enterprise. The enterprise competitive status characterizes the prerequisites adequacy for achieving a certain level of competitive advantages and depends on resource efficiency using.
Resource-activity approach as a basis of the competitive status formation foundation of mechanical engineering
Keywords: підприємства машинобудування; ресурси; потенціал; конкурентний потенціал; конкурентний статус; machine building enterprises; resources; potential; competitive potential; competitive status